Deconvolution of cargo delivery and immunogenicity following intranasal delivery of mRNA lipid nanoparticle vaccines - Mai N. Vu; Devaki Pilapitiya; Andrew Kelly; Marios Koutsakos; Stephen J. Kent; Jennifer A. Juno; Hyon-Xhi Tan; Adam K. Wheatley (Molecular Therapy: Nucleic Acids)
Intranasal vaccination aims to elicit mucosal immunity in the respiratory tract to better protect against respiratory infections (e.g., SARS-CoV-2 and influenza). Most vaccines, including recent COVID-19 mRNA lipid nanoparticles (LNPs), are optimized for intramuscular (i.m.) administration and typically perform poorly when delivered intranasally. Here, we prepared mRNA-LNPs using clinically approved ionizable lipids (ALC-0315, SM-102, and DLin-MC3-DMA) with or without a permanent cationic lipid (1,2-dioleoyl-3-trimethylammonium-propane [DOTAP]) to deliver a model immunogen (ovalbumin [OVA]) and CRE recombinase reporter mRNA. Using wild-type C57BL/6 and Ai14 reporter mouse models, we deconvoluted the effects of LNP formulation on mRNA cargo delivery and immunogenicity following i.m. or intranasal (i.n.) administration. After i.m. vaccination, mRNA-LNPs demonstrated transfection of muscle and immune cells in vivo, and consequently robust humoral immune responses. In contrast, mRNA-LNP delivery to the respiratory mucosa was poorly immunogenic, both in naive animals and in those with post-infection inflammation. Encouragingly, mRNA-LNPs efficiently transfected epithelial and immune cells within the lungs and expressed mRNA cargo could efficiently recall immunity in draining secondary lymphoid tissues. The addition of DOTAP led to enhanced recall responses. Decoding interplays of LNP formulations and their performance in vivo within specific tissue compartments will provide principles that can guide the rational design of mRNA-LNPs for maximal protection against respiratory diseases.